Pictures of time beneath: Science, heritage and the uses of the deep past - Champion, Erik (2012)
Book Review of Pictures of Time Beneath: Science, Heritage and the Uses of the Deep Past/Kirsty Douglas. CSIRO Publishing Collingwood, Victoria. 9780643097049